The ethical attitude of dentists scale: development and psychometric properties - Abbas Ebadi; Amirahmad Shojaei; Bagher Larijani; Mohammad Sadegh Akhoundi; Azam Khorshidian (Journal of Medical Ethics and History of Medicine, 2022)
One critical tactic that leads to a better understanding of the ethical status of dentists is to assess their ethical attitude by using an appropriate scale. This study aimed to design and evaluate the validity and reliability of the ethical attitude of dentists scale (EADS).This study was conducted based on a mixed‐method design. The first qualitative part of the study was conducted in 2019 and the items of the scale were produced from the ethical codes compiled in a previous study. In this part, the psychometric analysis was conducted. The reliability was evaluated by Cronbach's alpha coefficient and intraclass correlation coefficient. Factor analysis was used to assess the construct validity (n = 511), and the following three factors were extracted with a total variance of 48.03. (1) Maintaining the standing of the profession in relationships. (2) Providing dental services while maintaining trust in the profession, and (3) Providing information for the benefit of the patient.In confirmatory factor analysis, appropriate values were obtained for the goodness of fit indices, and Cronbach’s alpha was 0.68 - 0.84 for the various factors. Based on the results mentioned above, this scale showed an appropriate validity and reliability for measuring the ethical attitude of dentists.